Tradisi Botram dalam Dongeng Kabayan: Struktur dan Nilai Budaya sebagai Materi Ajar Interkultural BIPA - Elvi Zurviana; Tedi Permadi; Yulianeta Yulianeta (Badan Pengembangan dan Pembinaan Bahasa, 2025)
This study aims to analyze the narrative structure and cultural values contained in the botram tradition as represented in the Kabayan fairy tale, and examine its potential as an alternative intercultural teaching material in teaching Indonesian for Foreign Speakers (BIPA). Using a descriptive qualitative approach and AJ Greimas' structural analysis, this study explores the relationship between character action patterns, narrative structures, and moral messages embodied in the social practice of botram. Data collection techniques were carried out through text documentation in the form of three relevant Kabayan fairy tales, as well as a search for supporting literature on narrative theory, Sundanese culture, and intercultural learning. The data analysis process included data reduction, coding narrative elements, mapping actant structures and functional schemes, and interpreting cultural meanings based on Kluckhohn's value theory and Sundanese cultural experiences. The results of the analysis indicate that botram not only functions as a narrative element, but also as a symbol of social reconciliation that emphasizes the values of simplicity, solidarity, and balance in Sundanese life. These values serve as a medium for character formation and a means of internalizing collective ethics that are relevant for developing the intercultural competence of BIPA learners. These findings confirm that the integration of local traditions in language learning can enrich the learning process by providing authentic, reflective, and humanistic cultural experiences. Abstrak Penelitian ini bertujuan untuk menganalisis struktur naratif dan nilai-nilai budaya yang terkandung dalam tradisi botram (makan bersama) sebagaimana direpresentasikan dalam dongeng Kabayan, serta menelaah potensinya sebagai alternatif materi ajar interkultural dalam pengajaran Bahasa Indonesia bagi Penutur Asing (BIPA). Dengan menggunakan pendekatan kualitatif deskriptif dan analisis struktural A. J. Greimas, penelitian ini menelusuri hubungan antara pola tindakan tokoh, struktur naratif, dan pesan moral yang diwujudkan dalam praktik sosial botram. Teknik pengumpulan data dilakukan melalui dokumentasi teks berupa tiga dongeng Kabayan yang relevan, serta penelusuran literatur pendukung mengenai teori naratif, budaya Sunda, dan pembelajaran interkultural. Proses analisis data meliputi reduksi data, pengkodean elemen naratif, pemetaan struktur aktan dan skema fungsional, serta interpretasi makna budaya berdasarkan teori nilai Kluckhohn dan pengalaman budaya Sunda. Hasil analisis menunjukkan bahwa botram tidak hanya berfungsi sebagai elemen naratif, tetapi juga sebagai simbol rekonsiliasi sosial yang menegaskan nilai kesederhanaan, solidaritas, dan keseimbangan hidup masyarakat Sunda. Nilai-nilai tersebut berperan sebagai media pembentukan karakter dan sarana internalisasi etika kolektif yang relevan untuk pengembangan kompetensi interkultural pemelajar BIPA. Temuan ini menegaskan bahwa integrasi tradisi lokal dalam pembelajaran bahasa dapat memperkaya proses belajar dengan menghadirkan pengalaman budaya yang otentik, reflektif, dan humanistik.